2001
DOI: 10.1097/00042737-200106000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of chronic pancreatitis in the Czech Republic

Abstract: There have been only a few studies dealing with the incidence of chronic pancreatitis published. Over the last 80 years, original studies describing the incidence of chronic pancreatitis were undertaken, including studies in Scandinavia, Switzerland, Hungary and Poland. Incidence varied geographically, from 1.6 new cases per year among 100,000 inhabitants in Switzerland to 23 new cases among 100,000 inhabitants in Finland. The aetiology of 70% of all cases was alcoholic pancreatitis. The incidence of chronic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 6 publications
3
37
0
3
Order By: Relevance
“…In Western countries, in the period from 1940 to 2003, the frequency of alcohol as an etiological factor of chronic pancreatitis increased from 19% [6] to 50% [7] and even up to 80% [8,9] . The results of the latter study regarding the etiology of chronic pancreatitis were subsequently confirmed by others in Europe [10][11][12][13][14][15][16][17] as well as in Brazil [18] , Australia [19] and South Africa [20] . On the other hand, four consecutive surveys carried out in Japan (from 1970 to 1977, from 1978 to 1984, in 1994, and in 1999, respectively) [21] showed that alcohol as an etiological factor accounted for fewer than 60% of chronic pancreatitis cases in this country.…”
Section: Introductionsupporting
confidence: 61%
“…In Western countries, in the period from 1940 to 2003, the frequency of alcohol as an etiological factor of chronic pancreatitis increased from 19% [6] to 50% [7] and even up to 80% [8,9] . The results of the latter study regarding the etiology of chronic pancreatitis were subsequently confirmed by others in Europe [10][11][12][13][14][15][16][17] as well as in Brazil [18] , Australia [19] and South Africa [20] . On the other hand, four consecutive surveys carried out in Japan (from 1970 to 1977, from 1978 to 1984, in 1994, and in 1999, respectively) [21] showed that alcohol as an etiological factor accounted for fewer than 60% of chronic pancreatitis cases in this country.…”
Section: Introductionsupporting
confidence: 61%
“…Chronic pancreatitis (CP) is an inflammatory disorder most commonly associated with alcohol consumption [1][2][3][4][5][6][7][8][9] . Since 1982 [10], smoking has been recognized as a risk factor for CP, particularly in alcohol-related CP compared with CP arising from other causes [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence is 11.9/100,000 in Japan [5], 10/100,000 in Denmark [6], 6.4/100,000 in Germany [7], 7.7/100,000 in France [8] and 7.8/100,000 in the Czech Republic [9]. The limits of epidemiological surveys derive from the need for long-term followup and the variability of the severity of the disease [10].…”
Section: Discussionmentioning
confidence: 99%
“…A multicentre study from Italy showed that 34% of CP cases were caused by excessive alcohol consumption [16]. That figure was 65.4% in the Czech Republic [9], 44% in the US, 95% in Australia and 54% in Japan [15]. In the Hungarian cohort, total alcohol-related CP was 62% (45% of all CP cases consumed alcohol regularly and 18% admitted to occasional alcohol use).…”
Section: Discussionmentioning
confidence: 99%